Queer Media Productions in Social VR: Self-Expression, Documentation and Resistance Through VRChat - Roxo, Sérgio Cunha Galvão (AoIR Selected Papers of Internet Research, 2026)
Social Virtual Reality (Social VR) has become a crucial space for LGBTQIA+ individuals, fostering self-expression, representation, and community-building. Platforms like VRChat provide a digital refuge, enabling identity exploration and social connection through immersive interactions and customizable avatars. While existing research has primarily examined embodiment and community dynamics, little attention has been given to the digital media productions created by LGBTQIA+ users in Social VR. This study employs a digital and media ethnographic approach to analyze queer media content in VRChat, including documentaries, performances, tutorials, music videos, and erotic role-playing. Through content analysis, documental analysis, and interviews with queer creators, this research explores how VRChat functions as a site for queer worldmaking, documenting LGBTQIA+ experiences and expanding visibility. VRChat is a vital tool for "Embodied Visibility," where queer users utilize virtual embodiment to construct and express identities that may not be possible in offline spaces. Media productions within VRChat, categorized as "machinima" or "metaverse films", serve as archival records of queer life, resisting systemic erasure and affirming LGBTQIA+ existence. As LGBTQIA+ rights encounter growing threats, these digital productions emerge as forms of cultural preservation and resistance. By capturing and amplifying queer narratives in Social VR, creators challenge and disrupt dominant discourses through queer worldmaking, offering representation and visibility while shaping digital spaces.